REPRESENTASI MATEMATIS - Rangkuti, Ahmad Nizar (FORUM PAEDAGOGIK, 2014)
AbstractMathematical representative is part of mathematicalcommunication. Mathematical communication ability is one of standard of process that still need for growing and students have it. This standard of process must say while process of mathematic learning. Mathematical representative is a picture, translator, act of expressing, reappointment, institutionalization, or modeling of idea, concept, concept mathematic, and relationship between one configuration, construction, or situation of problem which from the students in medley type as effort to get clarify meaning, showing of comprehending, or to look for solution of the problem which there in front of us. Representative is not also to show the result, or product of new configuration or construction, but also process of thinking that is done for getting and comprehending the concept, campaign, and relationship of mathematic from one configuration.Kata kunci: Komunikasi matematis, dan Representasi matematis